Manganese / cobalt-based MOFs nano-enzyme with hollow structure as well as preparation method and application thereof

By using hollow structure manganese/cobalt-based MOFs nanoenzyme to monitor the total antioxidant capacity during black tea fermentation, the accuracy and rapidity of monitoring of black tea fermentation degree was solved, and accurate monitoring and quality improvement in black tea processing was achieved.

CN119680646APending Publication Date: 2025-03-25TEA RESEARCH INSTITUTE CHINESE ACADEMY OF AGRICULTURAL SCIENCES

Patent Information

Application Number
CN202411823752.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve accurate, fast and reliable monitoring of the fermentation degree of black tea, resulting in uncertainty and quality problems in the processing of black tea.

Method used

The hollow structure manganese/cobalt-based MOFs nanoenzyme is adopted to achieve rapid and visual analysis of the total antioxidant capacity during black tea fermentation process through ultraviolet visible spectrum and naked eye observation, and a model of the antioxidant capacity value and fermentation degree of black tea is constructed.

Benefits of technology

It realizes the accurate judgment of the fermentation degree of black tea, and has the advantages of simplicity, speed and visualization, and supports intelligent processing and quality improvement of black tea.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680646A_ABST
    Figure CN119680646A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese / cobalt-based MOFs nano-enzyme with a hollow structure as well as a preparation method and application thereof, and belongs to the technical field of preparation and application of novel nano-materials. According to the invention, ZIF-67 is used as a carrier, potassium permanganate is used as a manganese source, and the Mn / Co-MOF nano-enzyme with a hollow structure and highly dispersed manganese species is prepared through a loading-low temperature pyrolysis strategy. The antioxidant substances in the black tea can inhibit the oxidase-like activity of the hollow-structure manganese / cobalt-based MOFs nano-enzyme, so that the color of the system is changed, and based on the principle, the method for detecting the total oxidation resistance of the tea based on the hollow-structure manganese / cobalt-based MOFs nano-enzyme is established. Meanwhile, the method is used for monitoring the change of the total antioxidant capacity in the black tea fermentation process, a new method for judging the fermentation degree of the black tea is established in combination with data processing methods such as machine learning, and a new means is provided for improving the quality of the black tea and intelligently processing tea leaves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation and application of novel nanomaterials, and specifically relates to a hollow structure manganese / cobalt-based MOFs nanozyme, a preparation method and application thereof. Background Art

[0002] Black tea is one of the most popular beverages in the world, accounting for 78% of total tea consumption due to its unique flavor and huge potential health benefits. As globalization continues, more and more consumers expect to drink high-quality black tea. Therefore, the demand for modern technology that can effectively control the quality of black tea during processing is increasing day by day. The production process of black tea can be divided into four steps: withering, rolling, fermentation and drying, among which fermentation is the key step that directly affects the quality of black tea. At present, the quality of black tea fermentation often depends on experienced tea makers, who can judge whether the fermentation is successful by distinguishing the color and aroma of the tea leaves. However, personal judgment may be affected by the environment, mood and health status at the time, and it is difficult to make accurate and repeatable judgments on the degree of fermentation. Therefore, conducting accurate and rapid monitoring research on the degree of fermentation of black tea is of pioneering significance for realizing the intelligent processing of black tea and improving the quality of black tea.

[0003] Recently, scientists have developed some emerging rapid detection technologies to monitor the changes in the composition, color, and aroma of black tea during the fermentation process, so as to determine the fermentation degree of black tea. For example, invention patent CN 113484309A discloses a method for monitoring the fermentation degree of black tea by coupling a nano-colorimetric sensor with a high spectrum, CN 114166770A discloses a method for monitoring the fermentation quality of black tea based on nanoporphyrin solution phase ultraviolet-visible spectroscopy, CN 115236058 A discloses a method and system for identifying the fermentation degree of black tea based on Raman spectroscopy, and CN117705781A discloses a rapid detection method for the fermentation degree of black tea based on olfactory visualization and its application. Although the above methods can effectively determine the fermentation degree of black tea, baseline drift, low signal-to-noise ratio, etc. greatly hinder their practical application. Therefore, the development of a low-cost, simple and reliable method for detecting the fermentation degree of black tea remains a huge challenge.

[0004] In fact, the essence of black tea fermentation is the oxidation reaction of polyphenols with tea polyphenols as the core under the action of enzymes. By real-time monitoring of the changes in the total antioxidant capacity during the fermentation of black tea, it is possible to monitor the degree of oxidation of polyphenols in tea leaves, thereby achieving an accurate evaluation of the degree of black tea fermentation. Traditional methods for detecting total reducing capacity include the iron ion reducing capacity method (FRAP), FC determination method, etc., or combined with liquid chromatography, Fourier change infrared, electrochemical methods, etc. for quantitative analysis. However, these methods require large-scale analytical instruments, complex pre-treatment, specific reaction conditions, etc., cannot achieve rapid monitoring, and it is difficult to meet the needs of industrialized and intelligent black tea processing.

[0005] Nanozymes are a class of nanomaterials with biological enzyme activity. Compared with biological enzymes, nanozymes have broad application potential in the field of chemical analysis due to their high catalytic activity, high stability, low cost and large-scale production. As an emerging component in the field of nanozymes, metal organic framework (MOF) nanozymes are attracting more and more attention due to their unique physicochemical properties. Among the many nanozymes, MOFs materials with oxidase-like activity can be used in the absence of H 2 O 2 The redox reaction in biochemistry is simulated under the condition of medium, and it has a broader application prospect due to its more simplified operating environment. Patent CN118090718A discloses a method for detecting antioxidants based on cobalt-based nanoenzyme colorimetric sensor array. Using the synthesized cobalt-based metal organic framework material, a colorimetric sensor detection array is constructed by adding different chromogenic substrates and the antioxidant to be tested, which is used for the identification and detection of eight antioxidants (ascorbic acid, glutathione, cysteine, gallic acid, epicatechin, tannic acid, chlorogenic acid, caffeic acid) in food.

[0006] The present invention uses cobalt-based MOF (ZIF-67) as a carrier and potassium permanganate as a manganese source, and prepares a manganese / cobalt-based MOFs nanozyme with a hollow structure by low-temperature calcination in an air atmosphere. The nanozyme prepared by this method has a hollow structure, which is conducive to the transmission of substances, and the doping of manganese further improves its enzyme-like catalytic activity. 2 O 2 Under the above conditions, it has high oxidase-like activity and good stability. The hollow manganese / cobalt-based MOFs material is used as an efficient oxidase-like enzyme to monitor the changes in the total antioxidant capacity during the fermentation of black tea, and a model of the antioxidant capacity value of black tea and its fermentation degree is constructed, thereby realizing the accurate judgment of the fermentation degree of black tea, which has great practical application value. Summary of the invention

[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a hollow structure manganese / cobalt-based MOFs nanozyme, a preparation method and a technical solution for its application. The hollow structure manganese / cobalt-based MOFs nanozyme of the present invention has a high oxidase-like activity and can catalyze the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) molecules from colorless to blue. The antioxidant substances in black tea can inhibit the occurrence of this reaction, and there is a linear relationship between its total antioxidant capacity value and the absorbance value. Through ultraviolet visible spectroscopy and naked eye observation, a rapid and visual analysis of the total antioxidant capacity value is achieved. By simulating the fermentation process of black tea, tea samples with different fermentation times are collected, their total antioxidant capacity is tested, and a graph of the total antioxidant capacity changing with time is drawn. Combined with the results of sensory evaluation, a prediction model for the antioxidant capacity value of black tea and its fermentation degree is constructed, which is used for monitoring and evaluating the fermentation degree during the processing of black tea, and has good practical application value.

[0008] The present invention is specifically implemented by the following technical solutions:

[0009] The first aspect of the present invention provides a method for preparing a hollow structured manganese / cobalt-based MOFs nanozyme, which comprises the following steps: using ZIF-67 as a carrier and potassium permanganate as a manganese source, and preparing a Mn / Co-MOF nanozyme having a hollow structure and highly dispersed manganese species by loading-low-temperature pyrolysis.

[0010] Furthermore, the mass ratio of potassium permanganate to ZIF-67 is 0.1 to 1.0.

[0011] Furthermore, the load-low temperature pyrolysis condition is low temperature calcination in air, and the calcination temperature ranges from 200°C to 350°C.

[0012] The second aspect of the present invention provides a hollow structure manganese / cobalt-based MOFs nanozyme prepared by any of the above-mentioned preparation methods.

[0013] The third aspect of the present invention provides the use of the above-mentioned hollow structure manganese / cobalt-based MOFs nanozyme in detecting the total antioxidant capacity of black tea samples at different fermentation times.

[0014] Furthermore, the application specifically includes the following steps:

[0015] (1) Total antioxidant capacity values ​​are calculated based on the concentration of ascorbic acid;

[0016] (2) Collect black tea samples at different fermentation times, from the beginning of fermentation to 6 hours of fermentation, and collect samples every 20 minutes;

[0017] (3) Weigh 1 g of the sample obtained in step (2), add water and brew to obtain a black tea sample extract;

[0018] (4) Add acetic acid-sodium acetate buffer solution, hollow structure manganese / cobalt-based MOFs nanozyme solution, black tea sample extract obtained in step (3) and TMB solution to a 96-well plate in sequence, react at room temperature for 10 minutes, and analyze with an ultraviolet spectrophotometer. According to the change in the absorption peak intensity at 652 nm, the total antioxidant capacity of the black tea samples with different fermentation times is obtained.

[0019] The fourth aspect of the present invention provides the use of the above-mentioned hollow structure manganese / cobalt-based MOFs nanozyme in determining the fermentation degree of black tea.

[0020] Furthermore, the application specifically includes the following steps:

[0021] a) The black tea samples with different fermentation times were subjected to sensory evaluation by a professional tea evaluation team, and the black teas with different fermentation times were divided into three categories: under-fermented, moderately fermented, and over-fermented based on the scores of the sensory evaluation;

[0022] b) Using hollow structure manganese / cobalt-based MOFs nanozymes, the total antioxidant capacity values ​​of black tea samples with different fermentation times were obtained by ultraviolet spectrophotometer analysis, and the ultraviolet-visible absorption spectra of the antioxidant capacity values ​​of black tea samples with different fermentation times were used to construct a fermentation degree discrimination model. The ultraviolet-visible absorption spectrum was 550nm-750nm, and the top n discriminant functions were selected with a cumulative contribution rate of >95% to construct a qualitative prediction model for the fermentation degree of black tea. The discrimination rate of the prediction model was used as a model evaluation index, and the optimal parameters were selected to calculate and obtain the optimal solution;

[0023] c) The characteristic information of UV-visible absorption spectra of antioxidant capacity detection of black tea samples with different fermentation times was analyzed by hierarchical cluster analysis, linear discriminant analysis or machine learning.

[0024] The hollow structure manganese / cobalt-based MOFs nanozyme of the present invention has high oxidase-like activity, and ascorbic acid (antioxidant) can inhibit its activity. The specific determination steps are as follows:

[0025] (1) The hollow structure manganese / cobalt-based MOFs nanozyme was dispersed in water to prepare a solution with a concentration of 0.5 mg / mL.

[0026] (2) Add acetic acid-sodium acetate buffer solution, nanozyme stock solution obtained in step (1) and 3,3',5,5'-tetramethylbenzidine (TMB) solution to a 96-well plate in sequence and react at room temperature for 10 minutes. The colorless TMB is oxidized by the hollow structure manganese / cobalt-based MOFs nanozyme into its blue product (TMBox), and the solution changes from colorless to blue. After analysis by UV spectrophotometer, a strong absorption peak is found at 652nm.

[0027] (3) Add acetic acid-sodium acetate buffer solution, nanozyme stock solution obtained in step (1), 3,3',5,5'-tetramethylbenzidine (TMB) solution and ascorbic acid solution of different concentrations to a 96-well plate, and react at room temperature for 10 minutes. The ascorbic acid concentration is linearly related to the absorption peak intensity at 652 nm, and the ascorbic acid quantitative analysis method is obtained.

[0028] The beneficial effect of the present invention is that the relationship between total antioxidant capacity and fermentation degree is proposed based on the essential changes in the chemical composition during the fermentation of black tea. The hollow structure manganese / cobalt-based MOFs nanozymes prepared have ultra-high oxidase-like activity, which can achieve rapid and visual analysis of total antioxidant capacity, thereby providing a new method for monitoring the fermentation degree of black tea, which has the advantages of simplicity, rapidity, and visualization. It provides technical support for the intelligent processing and quality improvement of black tea. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 TEM image of hollow structure manganese / cobalt-based MOFs nanozyme;

[0030] Figure 2 Ascorbic acid detection for hollow structured manganese / cobalt-based MOFs nanozymes;

[0031] Figure 3 is the total antioxidant capacity value of black tea samples at different fermentation times;

[0032] Figure 4 This is the clustering map of fermentation degree of black tea samples with different fermentation time based on hierarchical cluster analysis;

[0033] Figure 5 To discriminate the fermentation degree of black tea samples with different fermentation times based on support vector machine analysis. DETAILED DESCRIPTION

[0034] In order to better understand the new method for detecting total antioxidant capacity and determining the fermentation degree of black tea by a hollow structure manganese / cobalt-based MOFs nanozyme in the present invention, the present invention is further described by examples below, but the application of the present invention is not limited to the following specific examples.

[0035] Example 1: Preparation of ZIF-67 dispersion solution

[0036] 2-Methylimidazole and Co(NO) in a molar mass ratio of 1:1 were added 3 ) 2 6H 2O were dissolved in 50 mL of methanol, stirred vigorously for 10 min, and then allowed to stand at room temperature for 24 h. After centrifugation at 10,000 rpm and washing several times, the purple solid powder was collected and dried at 60 °C to obtain ZIF-67. 0.5 g of ZIF-67 was dissolved in 40 mL of ethanol and stirred for 10 min to obtain a ZIF-67 dispersion solution.

[0037] Example 2: Preparation of hollow structure manganese / cobalt-based MOFs nanozymes

[0038] 5 mL of 100 mg / mL potassium permanganate solution was added to the dispersed solution obtained in Example 1, and stirring was continued for 5 h. After centrifugation, washing, and drying, the solution was further calcined in air at 200° C. for 2 h to obtain hollow structure manganese / cobalt-based MOFs.

[0039] Example 3: Preparation of hollow structure manganese / cobalt-based MOFs nanozymes

[0040] 2 mL of 100 mg / mL potassium permanganate solution was added to the dispersed solution obtained in Example 1, and stirring was continued for 5 h. After centrifugation, washing, and drying, the solution was further calcined in air at 200° C. for 2 h to obtain hollow structure manganese / cobalt-based MOFs.

[0041] Example 4: Preparation of hollow structure manganese / cobalt-based MOFs nanozymes

[0042] 1 mL of 100 mg / mL potassium permanganate solution was added to the dispersed solution obtained in Example 1, and stirring was continued for 5 h. After centrifugation, washing, and drying, the solution was further calcined in air at 200° C. for 2 h to obtain hollow structure manganese / cobalt-based MOFs.

[0043] Example 5: Preparation of hollow structure manganese / cobalt-based MOFs nanozymes

[0044] 5 mL of 100 mg / mL potassium permanganate solution was added to the dispersed solution obtained in Example 1, and stirring was continued for 5 h. After centrifugation, washing, and drying, the solution was further calcined in air at 300° C. for 2 h to obtain hollow structure manganese / cobalt-based MOFs.

[0045] Example 6: Preparation of hollow structure manganese / cobalt-based MOFs nanozymes

[0046] 5 mL of 100 mg / mL potassium permanganate solution was added to the dispersed solution obtained in Example 1, and stirring was continued for 5 h. After centrifugation, washing, and drying, the solution was further calcined in air at 350° C. for 2 h to obtain hollow structure manganese / cobalt-based MOFs.

[0047] Figure 1The TEM and element mapping of the hollow structure manganese / cobalt-based MOFs nanozyme obtained in Example 2 show that the manganese / cobalt-based MOFs nanozyme maintains the dodecahedral cubic structure of the precursor ZIF-67. During the low-temperature calcination process, a hollow structure is formed, which is beneficial to the transmission of substances and improves the catalytic activity. Figure 1 The elements C, N, Mn and Comapping diagrams are given, and it can be observed that N, Mn and Co are evenly distributed on the nanozyme, while the C element is mainly concentrated at the edge of the material, further confirming its hollow structure and the high dispersion of the Mn element.

[0048] Example 7: Highly sensitive detection of ascorbic acid by hollow structured manganese / cobalt-based MOFs nanozymes.

[0049] Ascorbic acid is an antioxidant that can effectively resist free radicals. It is also known as vitamin C and is very important for human health. Hollow structure manganese / cobalt-based MOFs nanozymes have high oxidase-like properties and can catalyze the oxidation of the chromogenic substrate 3,3',5,5'-tetramethylbenzidine (TMB) from colorless to blue product (TMBox), and the UV-visible absorption spectrum shows a strong absorption peak at 625nm. Ascorbic acid has the ability to scavenge free radicals, which enables them to inhibit the oxidase-like activity of hollow structure manganese / cobalt MOFs. Based on this principle, a detection method for ascorbic acid based on hollow structure manganese / cobalt-based MOFs nanozymes was established.

[0050] Add 10 μL of 1 mg mL 2 prepared in Example 2 to 590 μL of NaAc-HAc buffer (pH = 3.5). -1 Hollow structure manganese / cobalt-based MOFs nanozymes, then 200 μL of ascorbic acid solution of different concentrations and 200 μL of TMB (1 mM) were added in sequence, and the absorbance of the reaction system at 652 nm was measured after reacting at 37 ° C for 10 min. The experiment was repeated three times, and the average value and ΔA (ΔA = A 0 -A, A 0 A and A are the absorbance values ​​of the system without ascorbic acid and with ascorbic acid, respectively. Draw a standard curve of ascorbic acid.

[0051] Figure 2 The present invention is based on the hollow structure manganese / cobalt-based MOFs nanozyme oxidase characteristics for ascorbic acid detection UV-visible absorption spectrum and standard curve. The change of absorption peak is related to ascorbic acid concentration 0.01-0.2 μM (ΔA = 0.07367x + 0.00774, R 2 =0.997) and 0.5-120 μM (ΔA=0.00628x+0.03023, R 2=0.999)) has a good linear relationship. The detection limit (LOD) is 0.3nM. Thanks to the high oxidase-like catalytic activity of the hollow structure manganese / cobalt-based MOFs nanozymes, the established detection method for ascorbic acid has a wider detection range and a lower detection limit.

[0052] Example 8: Detection of the total antioxidant capacity of hollow manganese / cobalt-based MOFs nanozymes in black tea samples with different fermentation times

[0053] After rolling, the fresh tea leaves are fermented in an environment where the temperature and relative humidity are maintained at 28℃~30℃ and ≥90% respectively. The whole fermentation process lasts for 6 hours. Samples are collected every 20 minutes. The collected samples are immediately frozen with liquid nitrogen for the next step of testing. The total antioxidant capacity is expressed in mmol equivalent of ascorbic acid / g.

[0054] During the detection, 1 g of the sample was weighed, and water was added to obtain a black tea sample extract; acetic acid-sodium acetate buffer solution, the hollow structure manganese / cobalt-based MOFs nanozyme solution obtained in Example 2, a black tea sample extract and a TMB solution were added to a 96-well plate in sequence. After reacting at room temperature for 10 minutes, the total antioxidant capacity of the black tea samples with different fermentation times was obtained according to the change in the absorption peak intensity at 652 nm after analysis by ultraviolet spectrophotometer.

[0055] Figure 3 The graph of the total antioxidant capacity of tea samples changing with fermentation time is given. As can be seen from the figure, black tea fermentation is divided into three stages. In the initial stage (0min-60min), the total antioxidant capacity of tea samples increases from 262umolAA / g to 311umol AA / g. In the second stage (60min-240min), the total antioxidant capacity in tea leaves continues to decrease with time. In the third stage, as the fermentation time increases, the total antioxidant capacity in tea leaves remains basically unchanged (260min-340min). It can be seen that tea fermentation is a slowly changing process, and the total antioxidant capacity can be used as an indicator to judge the degree of fermentation. According to the scoring coefficient of the Gongfu black tea evaluation factor in GB / T23776-2018, the professional tea evaluation team conducted a sensory evaluation of the fermentation degree of the collected tea samples: samples fermented for 0min-160min were determined to be insufficiently fermented, samples fermented for 180min-240min were determined to be moderately fermented, and samples fermented for 260min-340min were determined to be over-fermented.

[0056] Example 9: Discrimination and prediction of the fermentation degree of black tea samples by hollow structure manganese / cobalt-based MOFs nanozymes

[0057] The total antioxidant capacity of black tea samples with different fermentation degrees was detected by hollow structure manganese / cobalt-based MOFs nanozymes, and UV-visible spectra were obtained. Hierarchical cluster analysis (HCA) was performed on the absorbance values ​​between 550nm and 750nm. Figure 4 As shown in the figure, the tea sample data with different fermentation times form independent clusters without any overlap or misclassification. The samples with different fermentation times can be well distinguished and are highly consistent with the results obtained from the sensory evaluation.

[0058] Example 10: Discrimination and prediction of the fermentation degree of black tea samples by hollow structure manganese / cobalt-based MOFs nanozymes

[0059] The total antioxidant capacity of black tea samples with different fermentation degrees was detected by hollow structure manganese / cobalt-based MOFs nanozymes, and UV-visible spectra were obtained. The absorbance values ​​between 550nm and 750nm were analyzed by support vector machine (SVM). 80% of the results were used for the training set and 20% for the validation set.

[0060] Figure 5 The results show that the SVM algorithm correctly distinguished tea samples with different fermentation times and successfully projected them into under-fermented, moderately fermented, and over-fermented groups. The accuracy of the training and test sets of the confusion matrix reached 93% and 94%, respectively. The results show that the method for detecting the total antioxidant capacity based on hollow structure manganese / cobalt-based MOFs nanozymes combined with machine learning algorithms can discriminate and predict the degree of fermentation during black tea processing.

Claims

1. A method for preparing a hollow structure manganese / cobalt-based MOFs nanozyme, characterized in that: The following steps are involved: Using ZIF-67 as a carrier and potassium permanganate as a manganese source, Mn / Co-MOF nanozyme with a hollow structure and highly dispersed manganese species was prepared by loading-low-temperature pyrolysis.

2. The method for preparing a hollow structure manganese / cobalt-based MOFs nanozyme according to claim 1, characterized in that: The mass ratio of potassium permanganate to ZIF-67 is 0.1 to 1.

0.

3. The method for preparing a hollow structure manganese / cobalt-based MOFs nanozyme according to claim 1, characterized in that: The load-low temperature pyrolysis condition is low temperature roasting in air, and the roasting temperature ranges from 200°C to 350°C.

4. A hollow structure manganese / cobalt-based MOFs nanozyme prepared by the preparation method described in any one of claims 1 to 3.

5. Application of the hollow structure manganese / cobalt-based MOFs nanozyme as described in claim 4 in detecting the total antioxidant capacity of black tea samples with different fermentation times.

6. The use according to claim 5, characterized in that The specific steps include: (1) Total antioxidant capacity values ​​are calculated based on the concentration of ascorbic acid; (2) Collect black tea samples at different fermentation times, from the beginning of fermentation to 6 hours of fermentation, and collect samples every 20 minutes; (3) Weigh 1 g of the sample obtained in step (2), add water and brew to obtain a black tea sample extract; (4) Add acetic acid-sodium acetate buffer solution, hollow structure manganese / cobalt-based MOFs nanozyme solution, black tea sample extract obtained in step (3) and TMB solution to a 96-well plate in sequence, react at room temperature for 10 minutes, and analyze with an ultraviolet spectrophotometer. According to the change in the absorption peak intensity at 652 nm, the total antioxidant capacity of the black tea samples with different fermentation times is obtained.

7. Use of the hollow structure manganese / cobalt-based MOFs nanozyme as described in claim 4 in determining the fermentation degree of black tea.

8. The use according to claim 7, characterized in that The specific steps include: a) The black tea samples with different fermentation times were subjected to sensory evaluation by a professional tea evaluation team, and the black teas with different fermentation times were divided into three categories: under-fermented, moderately fermented, and over-fermented based on the scores of the sensory evaluation; b) Using hollow structure manganese / cobalt-based MOFs nanozymes, the total antioxidant capacity values ​​of black tea samples with different fermentation times were obtained through UV spectrophotometer analysis. The characteristic information of UV-visible absorption spectra of the antioxidant capacity values ​​of black tea samples with different fermentation times were analyzed by hierarchical clustering analysis, linear discriminant analysis or machine learning, and a black tea fermentation degree prediction model was constructed. The discrimination rate of the prediction model was used as the model evaluation index, and the optimal parameters were selected to calculate and obtain the optimal solution.

Citation Information

Patent Citations

  • Method for monitoring fermentation degree of black tea through hyperspectral coupled nanocrystallization colorimetric sensor

    CN113484309A

  • Method for monitoring fermentation quality of black tea based on nano porphyrin solution phase ultraviolet-visible spectrum

    CN114166770A

  • Method for detecting antioxidant based on cobalt-based nano-enzyme colorimetric sensing array

    CN118090718A

Cited By

  • Hollow Mn-doped ZIF-67 composite electrode material and preparation method thereof

    CN121892160A

  • Hollow mn-doped zif-67 composite electrode material and preparation method thereof

    CN121892160B